DEVELOPMENT OF EFFECTIVE ADDITIVE MATERIALS FOR LUBRICANTS FROM SECONDARY RESOURCES - Abror Khakimov; Zarina Khakimova (European Science Publishing, 2024)
In the article are considered some questions of the creation new and hither efficient additive anticorrosion and depression of the action on base available and cheap raw materials resource. They are determined main practical features additive, are revealed kinetic regularities and mechanisms anticorrosion protection of the metallic details of the machines and designs. The chemical stability of lubricant defined the oxidation an probing them in bomb under pressure of the oxygen (8 atm) under 100oC or bore the probing in special ditch in thermostats under raised to temperature. About stabilities judged on the amount of the absorbed oxygen, at time and on growth acid number lubricant. It is installed that introduction designed additive in composition of lubricant brings about reduction of water, in consequence of hydrophylling compositions that also reduces the corrosion of the metallic parts mechanism.
Keywords: Additive, anticorrosion protection, syntheses, mechanism, depressor, cheese, resource, rheological, kinetics, velocity, viscosity.